2019
DOI: 10.21203/rs.2.13282/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meibomian Gland Dysfunction (MGD), as Diagnosed by Non-Contact Infrared Meibography, in Dogs with Ocular Surface Disorders (OSD): A Retrospective Study.

Abstract: Background:Meibomian gland dysfunction (MGD) is one of the possible conditions underlying ocular surface disorders (OSD). Prevalence of MGD in dogs affected by OSD has not yet been reported. We aimed to evaluate the prevalence of MGD among OSD canine patients, which had been assessed by non-contact infrared meibography and interferometry, and to identify MGD associated factors that might guide its diagnosis. Medical records of canine patients examined for OSD between 2016 and 2019 were reviewed. The frequency … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The current study found a TFBUT difference of 4.3 s between the treated group and the control group, and so, the relative increased presence of brachycephalic animals in the treatment group was unlikely to be significant enough alone to cause this vastly larger discrepancy in TFBUT values observed in the treated group. In addition, no differences have previously been identified for meibography parameters between brachycephalic and non‐brachycephalic dogs 15 . Therefore, in the current study the reference population was still a reliable comparison group, irrespective of the differences noted in skull conformation between groups.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The current study found a TFBUT difference of 4.3 s between the treated group and the control group, and so, the relative increased presence of brachycephalic animals in the treatment group was unlikely to be significant enough alone to cause this vastly larger discrepancy in TFBUT values observed in the treated group. In addition, no differences have previously been identified for meibography parameters between brachycephalic and non‐brachycephalic dogs 15 . Therefore, in the current study the reference population was still a reliable comparison group, irrespective of the differences noted in skull conformation between groups.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, no differences have previously been identified for meibography parameters between brachycephalic and nonbrachycephalic dogs. 15 Therefore, in the current study the reference population was still a reliable comparison group, irrespective of the differences noted in skull conformation between groups.…”
Section: Discussionmentioning
confidence: 92%
“…Advancing age is known to negatively impact ocular surface homeostasis in humans, affecting all components of the lacrimal functional unit 56 . Similar changes are also reported in brachycephalic dogs, 7,23,49,52,57,58 although further research is needed to better characterize ocular surface physiology in older animals. In turn, this knowledge would help veterinarians and pet owners to slow down or prevent ocular surface pathology in aging brachycephalic dogs.…”
Section: Anatomical and Physiological Abnormalities Of The Brachyceph...mentioning
confidence: 71%
“…For every additional year of life, the risk for dogs to develop KCS or corneal pigmentation each increases by 10%, 7 while the risk to develop MGD increases by 20% 52 . The latter is supported by a study that examined 46 Shih Tzus and noted that MGD was more common in the middle‐aged and old‐aged groups compared with the juvenile group 49 .…”
Section: Anatomical and Physiological Abnormalities Of The Brachyceph...mentioning
confidence: 88%
See 1 more Smart Citation